PATTERN OF PSYCHIATRIC DISORDERS AT HIGH ALTITUDE: A CROSS-SECTIONAL STUDY FROM SKARDU, PAKISTAN - Malik Awais Amin; Mustajab Alam; Muhammad Adil; Anam Manzoor Alam; Qasim Zia; Syed Noman Uddin (Journal of Pakistan Psychiatric Society, 2025)
OBJECTIVES To determine the frequency of different psychiatric disorders among patients reporting to psychiatry department and to study their association with age, marital status and education level. STUDY DESIGN Descriptive cross-sectional study. PLACE AND DURATION OF STUDY Department of Psychiatry, Combined Military Hospital (CMH) Skardu from September 2021 to February 2022. METHOD A total of one hundred adult individuals, between 21 to 40 years of age, presenting to the Psychiatry department at CMH Skardu, were enrolled in this study after taking written informed consent. All the patients were interviewed by consultant psychiatrist and diagnosis was based on International Classification of Diseases (ICD) version 10. RESULTS Out of a total of 100 patients, 81 (81%) were married and 19 (19%) were un-married. The mean age of the patients was 26.94 + 4.35 years. The most common psychiatric disorders among patients living at high altitude were depressive episode in 44 patients (44%), followed by adjustment disorders in 30 (30%), anxiety disorder in 12 (12%), dissociative disorder in 9 (9%) and mood disorder in 5 patients (5%). CONCLUSION Depressive episode and adjustment disorder were the most prevalent psychiatric disorders at high altitude.